1966
DOI: 10.1139/b66-117
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Numbers of Some Western Canadian Plants

Abstract: Chromosome numbers are presented for 97 taxa of western Canada. A total of 33 are reported for the first time, and of these, the chromosome numbers given for Xerophyllum(Liliaceae), n = 15, Menziesia (Ericaceae), n = 13, and Physostegia (Labiatae), n = 19, are the first for these genera. A brief discussion is given for a few of the taxa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

1968
1968
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 9 publications
3
10
0
Order By: Relevance
“…The haploid chromosome number "n"-due to presence of two ploidy levels, "x" is the proper term-of big sagebrush has been intensively studied (Barker and McKell 1986;Kelsey and others 1975;others 1979, 1981;McArthur and Sanderson 1999;McArthur and Welch 1982;Sanderson and others 1989;Stahevitch and Wojtas 1988;Taylor and Brockman 1966;Taylor and others 1964;. The results of all these studies agree that the base number of chromosomes for big sagebrush is 9 (n = x = 9; fig.…”
Section: Chromosome Number _____________________________________________mentioning
confidence: 80%
See 1 more Smart Citation
“…The haploid chromosome number "n"-due to presence of two ploidy levels, "x" is the proper term-of big sagebrush has been intensively studied (Barker and McKell 1986;Kelsey and others 1975;others 1979, 1981;McArthur and Sanderson 1999;McArthur and Welch 1982;Sanderson and others 1989;Stahevitch and Wojtas 1988;Taylor and Brockman 1966;Taylor and others 1964;. The results of all these studies agree that the base number of chromosomes for big sagebrush is 9 (n = x = 9; fig.…”
Section: Chromosome Number _____________________________________________mentioning
confidence: 80%
“…5.2) and 2n = 4x = 36 ( fig. 5.3) (Barker and McKell 1986;Kelsey and others 1975;others 1979, 1981;McArthur and Sanderson 1999;Sanderson and others 1989;Stahevitch and Wojtas 1988;Taylor and Brockman 1966;Taylor and others 1964;). …”
Section: Chromosome Number _____________________________________________mentioning
confidence: 97%
“…4), only a single consensus sequence from each individual was used in the network reconstruction for simplicity Genetica (2007) 130:19-34 29 Based on a cladistic analysis of morphological characters, Murrell (1994) divided the dwarf dogwoods into five lineages: Cornus canadensis, C. unalaschkensis, and C. suecica as distinct species, respectively, and C. canadensis > C. suecica and C. suecica > C. canadensis as two informal categories. Cornus unalaschkensis was considered a tetraploid derived from hybridization between two diploid species (C. canadensis and C. suecica) (Dermen 1932;Taylor and Brockman 1966;Clay and Nath 1971;Bain and Denford 1979). Cornus canadensis > C. suecica was considered the product of backcrossing of hybrids to C. canadensis, and morphologically more similar to C. canadensis.…”
Section: Discussionmentioning
confidence: 99%
“…In the most comprehensive study to date, Bain and Denford (1979) found evidence of polyploidy in C. unalaschkensis using root tip squashes for ten populations and guard cell size for five populations. However, Taylor and Brockman (1966) reported 2n = 22 for C. unalaschkensis, and Dermen (1932) and Clay and Nath (1971) reported chromosome numbers of 2n = 44 for C. canadensis. Polyploid taxa are often larger than their diploid relatives (Giles 1942;Grant 1981).…”
Section: Methodsmentioning
confidence: 99%
“…Using the results from this study, further work needs to be done in several areas. First, size variation, the existence of a putative tetraploid, and the conflicting chromosome counts of Dermen (1932), Taylor and Brockman (1966), Clay and Nath (1971), and Bain and Denford (1979) indicate that ploidy differences within and between species need to be investigated. Second, electrophoretic and/or molecular studies are needed to examine populational level variation.…”
Section: Cornus Canadensis > -C Suecica (Group B) Is the Product Of mentioning
confidence: 99%